Concerning Tension: Investigating the Nature of the Photograph - Matthews, Samantha (Auckland University of Technology, 2013)
This practice-based research project delves into a complex relationship that exists within photography. In the space between the photograph and what it represents there is a level of disconnect. This intangible space became the stimulus of my research, instigating a dialogue with the notion of tension. By investigating how tension is manifest and operates in the photographic image, the research seeks to not only converse with the tension existing in the photograph, but also propose a space for discourse with the medium of photography itself.
Keywords: The Photograph; Tension; Referent; Juncture; Residue; Resistance